Sītā's kitchen : a testimony of faith and inquiry - Gandhi, Ramchandra, 1937-2007 (Wiley Eastern, 1994)
On a structure dedicated to Sita (Hindu deity) in the disputed Babari Masjid (Faizabad, India), with observations on Hindu and Buddhist philosophies, and a suggestion to solve the Ramjanmabhumi-Babari Masjid controversy, by an Indian philosopher.